2007
DOI: 10.1142/s1088424607000242
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic aluminium(III) and gallium(III) corroles

Abstract: The preparation and spectroscopic properties of a series of metallocorroles with polar head groups CHO and CH = C ( CN )( COOH ) are reported, as well as the X-ray crystal structure of 5,10,15-tris(pentafluorophenyl)corrolatoaluminium(III)bispyridine (triclinic space group (P-1) with unit cell parameters: a = 9.426(1) Å; b = 13.202(1) Å; c = 19.936(1) Å; α = 74.19(1)°; β = 78.47(1)°; γ = 75.75(1)°; V = 2289.57(8) Å3). Amphiphilic aluminium(III) and gallium(III) corroles exhibit electronic absorption (Soret pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
5
20
0
Order By: Relevance
“…The crystal structure of the bis-pyridine aluminum(III) corrole 8 reveals that the metal ion is located in the plane of the corrole macrocycle and that the two axial pyridine molecules are nearly parallel to each other with a twist angle of 3.6 • [43]. Close inspection of the two pyridine molecules suggests that they bend slightly toward each other with a bending angle of 171.5 • .…”
Section: Aluminum(iii) Corrolesmentioning
confidence: 99%
“…The crystal structure of the bis-pyridine aluminum(III) corrole 8 reveals that the metal ion is located in the plane of the corrole macrocycle and that the two axial pyridine molecules are nearly parallel to each other with a twist angle of 3.6 • [43]. Close inspection of the two pyridine molecules suggests that they bend slightly toward each other with a bending angle of 171.5 • .…”
Section: Aluminum(iii) Corrolesmentioning
confidence: 99%
“…Of interest here is a gallium(III) complex, 1 [Ga(tpfc)] (32)(33)(34)(35), where tpfc represents the trianion of 5,10,15-tris(pentafluorophenyl)corrole [H 3 (tpfc)]. 1 is highly fluorescent, with an emission quantum yield far exceeding that of its zinc porphyrin analog (36)(37)(38). The macrocyclic ring of this complex can be selectively modified to afford molecules that exhibit a wide range of physical and chemical properties (1).…”
mentioning
confidence: 99%
“…The PMH were more susceptible to the cytotoxic effects of 1-Al -TiO 2 than the U87-Luc cells; it is reasonable that non-cancerous cells, especially primary cells, would be less tolerant towards exogenous non-native agents[48,49]. Nonetheless, the intense fluorescence exhibited by 1-Al [26,33] would allow for the potential use of the nanoconjugate 1-Al -TiO 2 as an optical imaging agent observable by confocal fluorescence microscopy even at low concentrations (0.02–2 µg/mL) below the cytotoxic thresholds for both cancerous and non-cancerous cells.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that 5,10,15-trispentafluorophenyl corrole and its derivatives exhibit bright and robust fluorescence signals in the near-IR region (λ em ≥ 600 nm) and are therefore considered suitable candidates for optical imaging[2023]. In addition, the chemical versatility of corroles, allowing for various metallation[2426] and substitution[27,28] reactions, as well as their biological stability[2931] make them attractive contrast agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation